The Skin Microbiome: Is It Affected by UV-induced Immune Suppression? - Patra, VijayKumar; Byrne, Scott N.; Wolf, Peter (Frontiers in Microbiology, 2016)
Human skin apart from functioning as a physical barricade to stop the entry of pathogens, also hosts innumerable commensal organisms. The skin cells and the immune system constantly interact with microbes, to maintain cutaneous homeostasis, despite the challenges offered by various environmental factors. A major environmental factor affecting the skin is ultraviolet radiation UV-R from sunlight. UV-R is well known to modulate the immune system, which can be both beneficial and deleterious. By targeting the cells and molecules within skin, UV-R can trigger the production and release of antimicrobial peptides (AMPs), affect the innate immune system and ultimately suppress the adaptive cellular immune response. This can contribute to skin carcinogenesis and the promotion of infectious agents such as herpes simplex virus and possibly others. On the other hand, a UV-established immunosuppressive environment may protect against the induction of immunologically mediated skin diseases including some of photodermatoses such as polymorphic light eruption. In this article, we share our perspective about the possibility that UV-induced immune suppression may alter the landscape of the skin's microbiome and its components. Alternatively, or in concert with this, direct UV-induced DNA and membrane damage to the microbiome may result in pathogen associated molecular patterns (PAMPs) that interfere with UV-induced immune suppression.